Comparison of pharmacokinetic and safety profiles between Bemfola(®) and Gonal-f(®) after subcutaneous application - Wolzt, Michael (Eur J Drug Metab Pharmacokinet, 2015)
Recombinant human follicle stimulating hormone (r-hFSH) is effective and safe for controlled ovarian stimulation. Bemfola(®) (Finox AG, Burgdorf, Switzerland), a new biosimilar r-hFSH, has proven comparable non-clinical pharmacological profiles to those of the widely used Gonal-f(®) (Serono Pharma S.p.A., Bari, Italy). The objective of this study was to show that Bemfola(®) yields comparable clinical pharmacokinetic (PK) and safety profiles to Gonal-f(®) in healthy female subjects. In this randomized, Phase I trial conducted in healthy female volunteers (N = 32), a 2-period, balanced 2-treatment crossover design was used. A single subcutaneous dose of 225 IU Bemfola(®) or Gonal-f(®) was administered in each treatment period per sequence. Blood was collected for pharmacokinetic analysis until 10 days after each r-hFSH treatment. For down-regulation of endogenous FSH subjects were given a depot injection with leuprolide acetate prior to the study drug in either sequence. Pharmacokinetic data was available for 23 subjects. No appreciable differences in key PK parameters were detected between the r-hFSH products as per non-compartmental PK analysis [i.e. for Bemfola(®) and Gonal-f(®) respectively AUC(0–192) 424.90 and 432.75 IU h/L, C (max) 0.98 and 0.95 IU/L, T (max) 24.0 h (range 6.0–24.0) and 24.0 h (range 9.0–24.0), t (1/2) 43.58 h [standard deviation (SD 14.17)] and 42.58 h (SD 16.47), and K (e) 0.0075 1/h (SD 0.003) and 0.0077 1/h (SD 0.002)]. Subgroup analysis for estradiol (E2) response was similar for Bemfola(®) and Gonal f(®) (AUC((0-–120)) p = 0.21 and C (max) p = 0.82). No major safety issues were identified and no immunogenic reaction to r-hFSH was observed. The results of this study indicate that a single dose of Bemfola(®) exhibits pharmacokinetic and safety profiles comparable to Gonal-f(®) in healthy young women.